Nurturing Future Teachers: Exploring Factors and Challenges in Board Performance of Beced Curriculum Graduates - Blessilda Grace C. Tigas; Glenda C. Magno, EdD; Rosemarie C. Farro, PhD (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
The Licensure Examination for Teachers (LET) is a crucial assessment mandated by Republic Act 7836 to regulate the teaching profession in the Philippines. At Bataan Peninsula State University Dinalupihan Campus, the Bachelor of Science in Early Childhood Education program follows CHED Memorandum Order No. 76, s. 2017. Under Republic Act 8981, the Professional Regulation Commission (PRC) grants licenses to LET passers. This study explored factors influencing Education Graduates' LET performance using a mixed-method approach. Results showed an 89% passing rate, with review attendance significantly impacting success. Personal factors such as time management, motivation, and balancing responsibilities played a key role. A proposed intervention plan aims to address challenges and enhance future LET performance.